Peasant pasts : history and memory in western India - Chaturvedi, Vinayak (University of California Press, 2007)
Provides an intervention in the social and cultural history of India by examining the nature of peasant discourses and practices during the 19th and 20th centuries. This book shows that peasants in Gujarat were active in production and circulation of political ideas. It argues that nationalists in Gujarat established power through use of coercion.